Heat waves effect on daily mortality in districts in Madrid: The effect of sociodemographic factors. (20th October 2021) - López-Bueno, JA; Díaz, J; Sáchez-Guevara, C; Sánchez-Martínez, G; Franco, M; Gullón, P; Núñez-Peiró, M; Linares, C
Abstract: Background: Although there is significant scientific evidence on the impact of heat waves, there are few studies that analyze the effects of sociodemographic factors on the impact of heat waves below the municipal level. Methods: The objective of this study was to analyze the role of income level, percent of the population over age 65, existence of air conditioning units and hectares (Ha) of green zones in districts in Madrid, in the impact of heat on daily mortality between January 1, 2010 and December 31, 2013. Seventeen districts were analyzed, and Generalized Linear (GLM) Poisson Regression Models were used to calculate relative risks (RR) and attributable risks (RA) for the impact of heat waves on mortality due to natural causes (CIEX:A00-R99). The pattern of risks obtained was analyzed using GLM univariates and multivariates of the binomial family (link logit), introducing the socioeconomic and demographic variables mentioned above. Results: The results indicate that heat wave had an impact in only three of the districts analyzed. In the univariate models, all of the variables were statistically significant, but Ha of green zones lost significance in the multivariate model. Income level, existence of air conditioning units, and percent of the population over age 65 in the district remained as variables that modulate the impact of heat wave on daily mortality in the municipality of Madrid. Income level was the key variable that explained this behavior. Conclusions: The results obtained in this study show that there are factors below the municipal level (district level) that should be considered as focus areas for health policy in order to decrease the impact of heat and promote the process of adaptation to heat in the context of climate change. Key messages: There are factors below the municipal level which should be considered for health policy in order to decrease health heat impacts. Privation hamper isolation of ageing people from extreme outdoor temperatures. Therefore, in some cases poverty could become the key risk factor that explain the vulnerability to heat waves.